2019
DOI: 10.1371/journal.pone.0218399
|View full text |Cite
|
Sign up to set email alerts
|

Aggrecan is required for chondrocyte differentiation in ATDC5 chondroprogenitor cells

Abstract: Aggrecan is an integral component of the extracellular matrix in cartilaginous tissues, including the growth plate. Heterozygous defects in the aggrecan gene have been identified as a cause of autosomal dominant short stature, bone age acceleration, and premature growth cessation. The mechanisms accounting for this phenotype remain unknown. We used ATDC5 cells, an established model of chondrogenesis, to evaluate the effects of aggrecan deficiency. ATDC5 aggrecan knockdown cell lines (AggKD) were generated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…Hellio observed that the FMOD expression was downregulated in the lateral meniscus at 3 weeks after anterior cruciate ligament transection for experimental OA in rabbits, but returned to normal at 8 weeks after surgery [67]. Aggrecan (ACAN) is a macromolecular proteoglycan and a crucial component of meniscus ECM, helping to maintain biomechanical properties of ECM [6871]. Favero et al found that OA meniscus and synovium could release inflammatory molecules to induce meniscus ACAN degradation and ECM loss [72].…”
Section: Discussionmentioning
confidence: 99%
“…Hellio observed that the FMOD expression was downregulated in the lateral meniscus at 3 weeks after anterior cruciate ligament transection for experimental OA in rabbits, but returned to normal at 8 weeks after surgery [67]. Aggrecan (ACAN) is a macromolecular proteoglycan and a crucial component of meniscus ECM, helping to maintain biomechanical properties of ECM [6871]. Favero et al found that OA meniscus and synovium could release inflammatory molecules to induce meniscus ACAN degradation and ECM loss [72].…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the synthesis and deposition of the ECM by immortalized Cant1 knock-out and wild-type chondrocytes, KO1, and WT6 cells were incubated for 12 days in DMEM containing 5% FBS in presence or absence of ITS. Insulin, contained in this serum substitute (as in Nutridoma-SP) together with transferrin and sodium selenite, promotes chondrogenesis in ATDC5 cells and favors the differentiated phenotype in immortalized human chondrocytes [21,23,28]. The ECM produced over 12 days was analyzed by Alcian blue staining, aggrecan Western blot, and immunofluorescence.…”
Section: Characterization Of the Extracellular Matrix Produced By Immortalized Cellsmentioning
confidence: 99%
“…To investigate the involvement of particular gene products in pathological mechanisms, these immortalized cells might be further modified by knocking down specific genes through RNA interference or gene editing. However, this approach, which have been reported in several cell lines such as ATDC5 [28] and Swarm rat chondrosarcoma cells [29], requires further subculturing to attain genetically modified clonal lines and, in addition, carries the risk of off-target effects. These problems can be overcome by the immortalization of chondrocytes from mouse models of genetic disorders of the skeleton to study putative disease pathways and/or ECM protein synthesis and assembly in simple and well-defined in vitro systems.…”
Section: Introductionmentioning
confidence: 99%
“…Another secreted CLR proteoglycan aggrecan [alternative names: Aggrecan 1 (AGC1), Chondroitin sulfate proteoglycan core protein 1 (CSPG1)], key ECM component of cartilaginous tissue [45], has similarly been found to be regulated by miRNAs. For instance, miR‐140 [46], miR‐92a [47], miR‐141‐3p [48] are involved in chondrogenesis via enhancing aggrecan expression.…”
Section: Mirna‐clr Axes In Developmental and Physiological Homeostasismentioning
confidence: 99%